Testing adaptive hypotheses on the evolution of larval life history in acorn and stalked barnacles. Issue 19 (18th September 2019) - Ewers‐Saucedo, Christine; Pappalardo, Paula
Abstract: Despite strong selective pressure to optimize larval life history in marine environments, there is a wide diversity with regard to developmental mode, size, and time larvae spend in the plankton. In the present study, we assessed if adaptive hypotheses explain the distribution of the larval life history of thoracican barnacles within a strict phylogenetic framework. We collected environmental and larval trait data for 170 species from the literature, and utilized a complete thoracican synthesis tree to account for phylogenetic nonindependence. In accordance with Thorson's rule, the fraction of species with planktonic‐feeding larvae declined with water depth and increased with water temperature, while the fraction of brooding species exhibited the reverse pattern. Species with planktonic‐nonfeeding larvae were overall rare, following no apparent trend. In agreement with the "size advantage" hypothesis proposed by Strathmann in 1977, egg and larval size were closely correlated. Settlement‐competent cypris larvae were larger in cold water, indicative of advantages for large juveniles when growth is slowed. Planktonic larval duration, on the other hand, was uncorrelated to environmental variables. We conclude that different selective pressures appear to shape the evolution of larval life history in barnacles. Abstract : In the present study, we assessed if adaptive hypotheses explain the distribution of the larval life history of thoracican barnacles within a strict phylogenetic framework. In accordance with Thorson's rule, the fraction of species with planktonic‐feeding larvae declined with water depth and increased with water temperature, while the fraction of species with nonplanktonic larvae exhibited the reverse pattern. In agreement with the "size advantage" hypothesis proposed by Strathmann in 1977, egg and larval size were closely correlated to each other, and settlement‐competent cypris larvae were larger in cold water, indicative of advantages for large juveniles when low temperatures slow development and growth.